Hibiscus Hibiscus Sheet Mask As A Natural Skin Care Alternative - Kristin Sangur; Nata Adinda Br Kaban (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Hibiscus sheet mask is a natural skin care solution made from hibiscus flower (Hibiscus rosa-sinensis L.). The purpose of this study was to analyze the physical, chemical, and organoleptic of hibiscus sheet mask as an alternative to natural skin care. This study used a red and layered hibiscus flower crown. Extracts were made using the maceration method. The results of the flower extract are then made in various variations of mask formulas. The Hibiscus sheet mask was then analyzed by 10 panelists for its physical, chemical and organoleptic. The results showed that the higher the concentration of hibiscus flower extract, the more it produced a mask that was red in color, had a hibiscus aroma and a thick texture. The higher the concentration of hibiscus flower extract, the more the mask has a low pH. Meanwhile, the panelists prefer the hibiscus sheet mask with the 75% formula (F3). Thus, the hibiscus sheet mask can be accepted by the panelists.